2011
DOI: 10.1371/journal.pone.0025319
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Gene Expression in the Artificial Human Trisomy Cells of Chromosome 8 Associated with Transformed Cell Phenotypes

Abstract: A change in chromosome number, known as aneuploidy, is a common characteristic of cancer. Aneuploidy disrupts gene expression in human cancer cells and immortalized human epithelial cells, but not in normal human cells. However, the relationship between aneuploidy and cancer remains unclear. To study the effects of aneuploidy in normal human cells, we generated artificial cells of human primary fibroblast having three chromosome 8 (trisomy 8 cells) by using microcell-mediated chromosome transfer technique. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 50 publications
3
54
0
Order By: Relevance
“…Studies of gene expression in yeasts and mammals in disomics or trisomics have reported differing results as to compensation and trans-effects (e.g., refs. [35][36][37][38] vs. claims of primarily dosage effects of the varied genes (e.g., refs. 39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of gene expression in yeasts and mammals in disomics or trisomics have reported differing results as to compensation and trans-effects (e.g., refs. [35][36][37][38] vs. claims of primarily dosage effects of the varied genes (e.g., refs. 39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed aneuploid model systems in several different species have accelerated research on the effects of aneuploidy per se. The physiological changes in response to an unbalanced karyotype are multifold, including impaired proliferation, replication stress and proteotoxic stress that is characterized by changes in protein stoichiometry, reduced protein folding capacity and by activation of autophagy [4][5][6][7][8][9][10][11][12][13]. The physiological response to aneuploidy goes hand in hand with a transcriptional response that is manifested in a conserved pathway deregulation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is quite common in the data for trisomic segments in other species. including Datura, barley, Arabidopsis, Drosophila, and human trisomic cells (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The ability to recover corresponding monosomics in maize facilitated the finding that this effect can be proportional through one, two, and three doses.…”
mentioning
confidence: 99%